Conservation Education on Several National Parks in Indonesia - E.K.S Harini Muntasib (Media Konservasi, 1999)
Conservation Education in National Parks is an activity to promote understanding and awareness on people directly or indirectly related to the National Parks who will then join the conservation effort. In this research, several conservation educations are recognized in some Indonesian National Parks. Almost all National Parks in Indonesia already carried out programs on Conservation Education, which kinds of activities is made to fit to thepreparedness of the organizing committee, fund and public responses. Generally, the pubiic gave positive responses on Conservation Education programs and have many opportunities to develop the activities.